EW 101 : a first course in electronic warfare - Adamy, David (Artech House radar library., 2001)
"EW 101 has been a popular column in the Journal of Electronic Defense for a number of years. This compilation of tutorial articles from JED provides introductory level electronic warfare instruction for students of the discipline."--